Microwave Dielectric Properties of Li3TiO3F Oxyfluorides Ceramics - Guoguang Yao; Jiuyan Zhao; Ya Lu; Hongkai Liu; Cuijin Pei; Qian Ding; Miao Chen; Yaming Zhang; Ding Li; Fu Wang (Crystals, 2023)
Using a solid-state reaction strategy, nominal Li3TiO3F oxyfluorides ceramics were fabricated, and its sintering behavior, microstructure, phase assemblages, as well as microwave dielectric performances were all investigated. The main phase of Li3TiO3F with cubic structures accompanied with small amounts of the LiF or Li2TiO3 secondary phase was identified by XRD analysis. SEM analysis showed that a uniform and dense microstructure was obtained for 750 °C-sintered samples. The dielectric constant (εr) and quality factor (Q × f) were found to be strongly correlated with porosity and grain size distribution, whereas the temperature coefficient of resonance frequency (τf) was mainly dominated by the phase assemblages. In particular, the 750 °C-sintered Li3TiO3F samples exhibited good microwave dielectric performances: εr = 18, Q × f = 57,300 GHz (under 9.2 GHz), τf = −43.0 ppm/°C.